2013
DOI: 10.1097/mpa.0b013e3182575fb5
|View full text |Cite
|
Sign up to set email alerts
|

Early Oral Refeeding Wisdom in Patients With Mild Acute Pancreatitis

Abstract: In patients with mild AP, EORF, with the subjective feeling of hunger, is safe, feasible, and reduces LOH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 14 publications
1
39
1
4
Order By: Relevance
“…Although not specifically studied in children undergoing ERCP, simple decisions such as when to initiate feedings in patients with pancreatitis have been shown to have great influence on length of hospitalizations. 17 These findings suggest that the severity of pediatric PEP may more accurately reflect post-ERCP management as opposed to the magnitude of injury to the pancreas. Complicating matters further is the frequent presence of confounding factors such as management of constipation and functional abdominal pain that often contribute to hospitalization length.…”
Section: Discussionmentioning
confidence: 93%
“…Although not specifically studied in children undergoing ERCP, simple decisions such as when to initiate feedings in patients with pancreatitis have been shown to have great influence on length of hospitalizations. 17 These findings suggest that the severity of pediatric PEP may more accurately reflect post-ERCP management as opposed to the magnitude of injury to the pancreas. Complicating matters further is the frequent presence of confounding factors such as management of constipation and functional abdominal pain that often contribute to hospitalization length.…”
Section: Discussionmentioning
confidence: 93%
“…Thirty-three articles (21 articles containing patients suffering from SAP as well as 12 articles with MAP patients) were selected. They contained two nonrandomized and 31 randomized controlled clinical trials (Table 2) [16][17][18][19][20][21][22][23][24][25][26][27]29,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Finally, statistical analyses were performed on data from articles where both EN and NPO groups were presented, the trial was randomized, and the relevant data were available.…”
Section: Inclusions and Exclusionsmentioning
confidence: 99%
“…This involves assessing and improving patient-reported health outcomes by taking into account the patients' own objectives, values, and preferences [3,6,7]. In a previous trial, we found that early oral refeeding (EORF), based on hunger, without remission of symptoms or normalization of biochemical markers, in patients with mild AP was safe and reduced the total hospital length of stay (6.8 AE 2.1 versus10.4 AE 4.1 d; P < 0.01) and post refeeding hospital length (2.30 AE 1.60 versus 3.27 AE 0.61 d; P < 0.01) compared with the traditional oral refeeding group [8]. Subjective feelings of hunger, therefore, may reflect recovery from gastrointestinal dysfunction and indicate that patients are ready to try oral feeding.…”
Section: Referencesmentioning
confidence: 81%